Contact mechanics of highly loaded counterformal finite line contacts: semi-infinite and layered elastic solids - Patricia Johns-Rahnejat; Nader Dolatabadi; Homer Rahnejat (2023)
Increasingly, machines operate under harsh contact conditions with high normal contact loads and tangential traction. This leads to increased wear and contact fatigue. Sub-surface stresses are responsible for premature contact fatigue failure of rolling element bearings, meshing gear teeth and cam-follower pairs. Consequently, surface protection measures, including hard wear-resistant coatings, have become commonplace. The choice of protective layers, method of fabrication, geometry and contact conformity affect fatigue performance. Traditionally, the prediction of contact integrity has been made using classical Hertzian contact mechanics. However, the theory is only applicable when the contact of a solid pair may be considered as an ellipsoidal indenter penetrating a semiinfinite elastic half-space, which is not the case for thin coatings. The paper provides comprehensive generic contact mechanics analysis with induced subsurface stresses in concentrated counterformal contacts for both semi-infinite and layered bonded elastic solids at high loads.